A centennial review of the English regional question: Whose policy space is it?. Issue 2 (15th March 2022) - Ziafati Bafarasat, Abbas; Baker, Mark
ABSTRACT: The Regional Authority Index emphasizes the emergence of sub-national regions in Europe at the expense of central government but this does not chime with dynamics of regional governance in England. Seeing governance as a construct of the central state for masked steering of sub-national democratic establishments whose 'side-effects' (new political identities) are then addressed by the central state through a cyclical rescaling of governance, we explore this inconsistency. Our centennial review of sub-national governance in England challenges the concept of networked polity whereby the unconditional role of the state is to empower stakeholders and facilitate cooperation amongst them. Although sub-regional governance currently seems to have become a cross-party approach to local management, the central state may continue to promote alternative governance scales in the future to (I) break down resultant sub-regional political identities threatening central policy; and (II) maintain its influence on local governments in relation to economic objectives.